Efisiensi Manajemen Pendidikan: Peran Kepemimpinan Kepala Sekolah di SMAN 11 Batanghari - Muhammad Rasyid (JMiE (Journal of Management in Education), 2024)
This study aims to analyze management efficiency at SMAN 11 Batanghari and to identify the factors that influence it. A qualitative descriptive approach was employed, with data collected through interviews, observations, and documentation. The research subjects included the principal, vice principal, teachers, and the management team. The findings reveal that the principal demonstrates high integrity in both mental and physical aspects, accompanied by strong self-concentration, which serves as a key asset in managing time and utilizing unique capacities optimally. Factors influencing management efficiency include individual characteristics, work focus, availability of facilities, relationships between the management team and teachers, professionalism, and academic background. These results highlight that management efficiency in schools is strongly determined by the leadership of the principal, the quality of human resources, and adequate infrastructural support.